EXPLORASI KEPEMIMPINAN KEPALA SEKOLAH BERBASIS TRI PARARTHA DI SEKOLAH DASAR KOTA SINGARAJA BALI - sukmayasa, hendra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
This study aims to: 1) determine whether school principals in Singaraja City internalize and apply the values of Tri Parartha in their leadership practices, 2) determine whether Tri Parartha-based leadership influences teacher performance, and 3) provide recommendations for the development of educational leadership models and research based on Balinese local wisdom, specifically Tri Parartha. This research is phenomenological, utilizing a mixed-methods research design. The respondents/subjects of this study were 14 elementary school principals in Singaraja City. The data collection method used in this study was interviews, and the instrument used was an interview guide. The data obtained from the interviews were analyzed using descriptive quantitative and descriptive qualitative analysis. Based on the research conducted, it is concluded that: 1) the majority (78.6%) of elementary school principals in Singaraja, Bali, have implemented Tri Parartha-based leadership in their professional duties, 2) Tri Parartha-based school principal leadership has a high influence on teacher performance in elementary schools, and 3) it is essential to determine the extent of the influence or contribution of Tri Parartha-based principal leadership on elementary school teacher performance, considering that related research has never been conducted in some schools.